Peran UMKM pada Olahan kripik Apel untuk Mendorong Pertumbuhan Ekonomi lokal Kota Batu Malang - Hikma Hikma; Wilda Wilda; Novianti Dewi Lestari; Nira Ramadhani M; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study examines the contribution of micro, small, and medium enterprises (MSMEs) in apple chip processing to local economic development in Batu City, Malang. Batu City, a major apple-producing region in Indonesia, has high prospects for developing apple-based processed products, including apple chips. The study was conducted using a qualitative descriptive method involving interviews, field observations, and documentation. The research findings revealed that the apple chip business has a significant impact on absorbing local workers, increasing residents' incomes, and establishing the image of a regional specialty product. These MSMEs also encourage creativity in product development, improving packaging design, and expanding distribution networks through digital platforms as a form of transformation towards a creative economy. However, there are obstacles such as limited access to capital, weak business management skills, and high competition in the market. The study's conclusions confirm that apple chip MSMEs play a crucial role in advancing the creative economy in Batu City. Therefore, government intervention is needed in the form of training programs, assistance with marketing access, and the development of policies that strengthen the MSME ecosystem for sustainable local economic growth.